Die Kultivierung von Deckenmooren im Rahmen der Intensivierung der Landwirtschaft Nordirlands: Hill Land Reclamation Scheme - Leister, Ingeborg (ERDKUNDE, 1955)
Like the rest of the island Northern Ireland is a country of small farm holdings. 80 per cent, of the farms do not exceed 50 acres in size. The poorer districts suffer from lack of facilities for supplementary part-time occupations. After a period of widespread neglect of agriculture and its needs - experienced also outside Northern Ireland -World War II brought about a considerable change. The greater prosperity of the farmers resulted in an increasing tendency towards application of improved farming techniques. This holds true especially for the eastern counties of Northern Ireland; the western counties, however, were unable to keep pace with this development. Their distance from Belfast, the economic centre and main port of the country, is greater and, in addition, Lough Neagh acts as a traffic barrier. Yet the comparatively poor transport facilities are also the result of the nature of the district, owing to which agriculture has to surmount greater difficulties than in the east. The soils are of a poorer quality and the proportion of waste land (barren mountain, bog and rough grazing) is exceptionally high. The farmers are too poor to do any reclamation-work worth mentioning themselves. The government, intent on promoting agriculture, especially in these districts, launched the Hill Land Reclamation Scheme in 1946, to be applied in the counties of Tyrone and Londonderry. The aim of the scheme is to reclaim those parts of the blanket-bogs, covering wide stretches of these two counties, which are capable of mechanical reclamation. Thereby, rough grazing land, up to now of scarcely any value, is being turned into pasture of full agricultural value.